Enhancing Trade Secret Protection amidst E-commerce Advancements: Navigating the Cybersecurity Conundrum - Disemadi, Hari Sutra; Budi, Henry Soelistyo (Sekolah Tinggi Hukum Bandung, 2023)
The e-commerce ecosystem has encompassed various aspects of life, giving rise to legal implications, particularly in the areas of intellectual property and personal data protection, which are now inseparable from Indonesia”™s economic system in the digital age. This research aims to elucidate the legal relationship between trade secrets as a crucial form of intellectual property to be safeguarded in the digital era and analyze Indonesia”™s legal capability to protect trade secrets amidst the escalating challenges of cybersecurity due to the widespread use of various forms of e-commerce. The research employs a normative legal research method to analyze the protection and legal certainty concerning trade secrets, which can be subject to unauthorized access or theft through cyberattacks. Utilizing a legislative approach, the research relies on secondary data in the form of primary legal sources. The findings of this research reveal political-legal issues and normative shortcomings in regulating e-commerce and trade secrets, often underestimating the digital threats that can harm individuals”™ intellectual property rights.